The Blue Man and Other Stories of the Skin - ROBERT NORMAN (University of California Press, 2014)
This book focuses on the dynamic qualities of the skin and the people who inhabit it. Included are stories about the life of the skin, tales of fascinating and mysterious patients, meditations on cultural issues including skin color, and thoughts about the future of the skin. I try to speak for the skin, since it cannot speak for itself, and show you how lucky we are to have such an amazing natural covering. Our skin is our partner, nourishing and protecting us, teaching us about the world,